2017
DOI: 10.2196/humanfactors.7196
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Patients With Chronic Obstructive Pulmonary Disease and Their Physiotherapists Regarding the Use of an eHealth Intervention

Abstract: BackgroundIf eHealth interventions are not used (properly), their potential benefits cannot be fulfilled. User perceptions of eHealth are an important determinant of its successful implementation. This study examined how patients with chronic obstructive pulmonary disease (COPD) and their physiotherapists (PHTs) value an eHealth self-management intervention following a period of use.ObjectiveThe study aimed to evaluate the perceptions of COPD patients and their PHTs as eHealth users.MethodsIn this study, an eH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
5
16
1
2
Order By: Relevance
“…This is in contrast to a 4-week pilot (telecoaching) study which showed a positive relationship between the degree of adherence of wearing a smartphone-based activity coach and the benefits from the intervention during the first two weeks albeit this association disappearing during the third week [10]. Despite a high degree of adherence with the PA telecoaching program (89.0% of the days used) in the trial by Vorrink and colleagues [20], the program was not able to induce significant improvements in PA [7]. The latter might be partly explained by the low degree of adherence of the primary care physiotherapists (due to financial reasons and time constraints) in using the foreseen website to adjust the patient's PA goals and to send motivating messages to the patients, which highlights the importance of introducing (semi-)…”
Section: Association With the Effectiveness Of The Interventioncontrasting
confidence: 74%
See 1 more Smart Citation
“…This is in contrast to a 4-week pilot (telecoaching) study which showed a positive relationship between the degree of adherence of wearing a smartphone-based activity coach and the benefits from the intervention during the first two weeks albeit this association disappearing during the third week [10]. Despite a high degree of adherence with the PA telecoaching program (89.0% of the days used) in the trial by Vorrink and colleagues [20], the program was not able to induce significant improvements in PA [7]. The latter might be partly explained by the low degree of adherence of the primary care physiotherapists (due to financial reasons and time constraints) in using the foreseen website to adjust the patient's PA goals and to send motivating messages to the patients, which highlights the importance of introducing (semi-)…”
Section: Association With the Effectiveness Of The Interventioncontrasting
confidence: 74%
“…They had a positive perception and rated their satisfaction in line with previous PA telecoaching research in a mixed COPD and diabetes type 2 population [19]. As reported by others [20], the majority of patients stated that the PA telecoaching intervention in this trial coached them towards improving their PA.…”
Section: Acceptability and Appropriatenesssupporting
confidence: 73%
“…In this study, videos were suggested as important measures for communicating the self-management interventions as well as for addressing questions about the shame associated with a self-inflicted disease. Previously reported eHealth interventions have involved persuasive technologies such as remote monitoring of physical activity [ 21 ] and self-monitoring of health values [ 50 ], but no such components were suggested by the people with COPD in our study. However, the absence of such proposals and desires is hardly surprising as it might be necessary to have knowledge about such interventions in order to propose them.…”
Section: Discussionmentioning
confidence: 55%
“…Both people with COPD and physiotherapists (PTs) have been shown to perceive an eHealth self-management application that intends to increase physical activity by goal-setting, advises on how to perform physical activity, and presents physical activity in steps to be stimulating and beneficial. However, PTs reported a low use of the eHealth application because of time constraints and costs [ 21 ]. More knowledge is needed about how eHealth tools should be designed to support the aspects of self-management other than physical activity that will meet the needs and expectations of health professionals and people with COPD and their relatives.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies and systematic reviews have been published regarding telemonitoring, mHealth and eHealth interventions in the management of COPD, with sparse evidence demonstrating positive improvements for patient self-management or treatment outcomes [21][22][23][24][25]. Issues with the development of self-management digital health interventions in COPD and for chronic diseases in general have been discussed [22,26].…”
Section: Introductionmentioning
confidence: 99%